The first results of processing observations of SS bodies from AI AS RUz photographic plate collection using the new technique - Yizhakevych, O. M.; Andruk, V. M.; Yuldoshev, Q.; Pakuliak, L. K.; Muminov, M. M. (Одеські астрономічні публікації, 2018)
The paper presents the first results of processing of photographic observations of SS bodies based on materials from the collection of plates of the Ulug Bek Astronomical Institute of theAcademyofSciencesof theRepublicofUzbekistan(AI ASRUz). The glass archive of the AI AI ASRUz has about 15 thousand photographic plates with images of various space objects. In this paper, we discuss the first results of processing of major planets’ photographic observations inUzbekistanusing the new technique. The observations were carried out on two astrographs –Tashkentnormal astrograph (TNA, D/F=330/3438) and Kitab Double Zeiss astrograph (DAZ, D/F=400/3000) in 1895-2004. Currently, in AI the work runs to streamline the archive and create a database of observations in a single xls-format. The number of photographic plates with images of major planets obtained on two telescopes is more than 300 negatives. In 2017, together with MAO NAS ofUkraine, the processing of these photographic observations using the new methodology was started. The plate digitization is performed on the flat-bed 10000XL in 1200dpi mode. Positions and photometric estimations in B-color of all registered on the plate objects are obtained using the software proposed and developed in MAO NAS of Ukrainerunning in LINUX/MIDAS/ROMAFOT environment. The search for major planets and their satellites among the whole set of plate objects and the comparison of their observed and predicted positions is carried out online with the help of internet-service (http://lnfm1.sai.msu.ru/neb/nss/nssephmr.htm). Up to date, the small part of the plate collection is treated, namely 23 negatives with images of Uranus, Neptune, Pluto and Saturn’s satellites, obtained on the Kitab DAZ astrograph. 16 negatives with 19 exposures gave the best results with (О-С) in the range ±1.5″. In total, we obtained 47 astrometric positions of the objects of interest in the wide interval of brightness’s (8m ±16m). The internal positional accuracy of the catalog in the Tycho-2 reference system is σαδ= 0.08″–0.13″, the photometric error of B-magnitudes is estimated as σB = 0.2m.